PRIMEROS ANTECEDENTES SOBRE LO INFINITAMENTE PEQUEÑO - Castro Chadid, Iván; Departamento de Matemáticas Facultad de Ciencias Pontificia Universidad Javeriana, Bogotá (2004)
The mathematical concept of something infinitely small was achieved thanks to arduous work of humanity throughout many centuries. The first  achievements related to the topic exist, fundamentally, because of the developments obtained by the atomists, being their most important  exponers Democritus, Zenon and Arquimedes in ancient Greece, and  Galilleo and Cavalieri in the Renaissance. The methods used by Arquimedes and Cavalieri to approach this problem, from their own perspectives, are presented here.